Addictive behaviour of students: Early detection experience and socio-psychological characteristics - A. V. Smirnov; L. A. Maksimova; I. A. Simonova (Образование и наука)
Introduction. Today, there is an increase in the risks of involving minors in various forms of deviant behaviour, among the varieties of which addictive behavioural models are particularly dangerous. In this regard, proactive preventive measures are becoming particularly relevant, among which one of the key areas is the timely identification of potential addicts, including among students of educational organisations.Aim. The aim of the study was to identify the actual socio-psychological characteristics of the personality of underage students who are prone to addictive behaviour.Methodology and research methods. The comparative-analytical method of working with scientific literature presented in eLIBRARY.RU, Scopus, Web of Science and Google Scholar databases was used as the main theoretical method. When organising the study, the authors relied on a number of methodological provisions: the structural method, when the research material is interpreted in accordance with the specific characteristics of the object of study; the method of comparisons, which consists in comparing individual results with each other. The main empirical method was the testing method. To obtain the results of the study, the authors employed a unified methodology of socio-psychological testing aimed at the identification of the risk of formation of addictive behaviour in minors. For mathematical and statistical data processing, the Statistics SPSS 19.0 package was applied: the Kolmogorov-Smirnov Dmax criterion (for boys and girls separately and jointly), the Mann-Whitney U test, regression analysis, analysis of averages, confidence and percentile intervals. Also, the factor analysis method was used – the principal component method, Varimax rotation. The stability of factors was calculated using the Lewandowski’s method. The study was conducted in different regions of Russia in 2019–2020. The sample consisted of 6,300 people.Results. Based on the analysis of scientific sources, the authors described the epidemiological picture of various forms of addictive behaviour of minors, the differences between male and female samples (young men demonstrate a greater desire for leadership, protest reactions, rivalry, and girls are more anxious, frustrated, focused on internal experiences), the interrelationships between the scales of the methodology and the poles of the selected factor structure from the point of view of asociality and prosociality of juvenile behaviour (desire for risk, social maladjustment, avoidance of conflict and others).Scientific novelty. The scientific novelty of the results is due to the receipt of relevant data on the specifics of the socio-psychological characteristics of modern adolescents and young men prone to addictive behaviour.Practical significance. The practical significance lies in the fact that the identified socio-psychological characteristics of the behaviour of a person prone to addictive behaviour can become the main planning work on the early detection of a tendency to addictive behaviour, organisation of preventive work with imperfect-year-olds, as well as for the organisation of psychological work with students at risk.